Effectiveness of stevia as a mouthrinse among 12-15-year-old schoolchildren in Nellore district, Andhra Pradesh - A randomized controlled trial - Kuna Vandana; Vuyyuru Chandrasekhara Reddy; Kudlur Maheswarappa Sudhir; Krishna Kumar; Saraswathi Harikrishnam Raju; Javvaji Narendra Babu (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of this study is to determine the effectiveness of stevia as a daily mouthrinse among 12-15 year-old schoolchildren in Nellore District, Andhra Pradesh. Materials and Methods: A randomized, controlled triple blind trial was carried out among 108 children in B. V. S Municipallity Girls High school in Nellore. Children were randomly allocated into four groups comprising 27 in each group. Four mouthrinses composed of 0.2% chlorhexidine gluconate; 0.05% sodium fluoride, 10.6% stevioside and placebo were provided to the study participants. Plaque index, gingival index, and International Caries Detection and Assessment System (ICDAS) II, respectively, were used for assessing oral condition. The mouthrinsing was carried out for 6 months. Results: Group C showed maximum reduction of 8% and 10% on plaque and gingival scores, respectively, followed by Group A and Group B. However, Group D participants showed 1.5% and 1.8% increase in plaque and gingival scores, respectively. Analysis of ICDAS scores at 6 months indicated that values recorded were same as baseline for all the three groups except that for Group D, there was an increase in the prevalence of cavitated lesion D2-6from 5.6% to 5.8%. Conclusion: Stevia demonstrated very potent antiplaque and antigingivitis properties as compared to other mouthrinses at the end of 6 months trial.